Enhancing Young Learners’ English-Speaking Skills through Suggestopedia Integrated with Plotagon Animation - Gina Afkara Nabila; Dodi Mulyadi; Testiana Wijayatiningsih (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This classroom action research had two objectives: (1) to describe the implementation of Suggestopedia integrated with Plotagon, and (2) to explore students' perspectives on the integrated instruction. The population comprised all 20 male students enrolled in the selected fifth-grade class at a private elementary school in Central Java during the 2024-2025 academic year; all students were included through total sampling. Following Kemmis and McTaggart's cycle of planning, action, observation, and reflection, the intervention comprised four 45-minute meetings: two meetings in Cycle 1 and two in Cycle 2. Quantitative data were obtained from pre-test, cycle-level formative assessment, and final post-test scores; while qualitative data from structured classroom observations, questionnaires, and semi-structured interviews were used to explain the implementation process and students' responses. Success was defined as at least 75% of students scoring 70 or above, accompanied by observable improvement in fluency and participation. Cycle 1 implemented vocabulary preparation, repeated animated-dialogue viewing, shadow reading, and scripted role-play; Cycle 2 added simple-past scaffolding, dialogue adaptation, and improvisational performance. The mean score increased from 60.75 on the pre-test to 73 after Cycle 1 (11/20 students, 55%, met the criterion), 80.75 on the Cycle 2 formative assessment (14/20, 70%), and 86 on the final post-test (16/20, 80%). Thus, the mastery criterion was reached at the final post-test. Qualitative evidence indicated greater confidence, participation, vocabulary recall, and fluency, although explicit grammar instruction temporarily reduced enthusiasm for some students. Because only aggregate scores were available, no inferential statistical test was reported.